VOLLEYBALL AS A MEANS OF DEVELOPING THE PHYSICAL QUALITIES OF CADETS OF THE ACADEMY OF THE REPUBLIC OF UZBEKISTAN - Kdirovа Mukhabbat Allaniyazovna (PEDAGOGS, 2024)
Annotation. Physical education in higher education is a particularly significant part of the educational process, which has a positive effect on the general condition of the student's body as a whole. This article examines the impact of physical activity in the form of playing volleyball on the development of physical qualities of university students. Improving the ways and methods of playing volleyball is an urgent issue. That is why the purpose of the article is to consider exercises that help in preparing for the game of volleyball, thereby affecting the physical qualities of students.